Drought Management for the Rainfed Areas in Thailand: A Case Study of October 2019 to April 2020 Period - Patsinghasanee, Supapap (Srinakharinwirot University Engineering Journal, 2020)
The annual rainfall uncertainty affects the available water. Therefore, in Thailand the available water during the dry season is the most important resources in rainfed areas for implementing the water management plan. Additionally, the most affected areas are in the rainfed areas since there is a deficiency of irrigation projects and water management plans. Consequently, the water balance process is necessary to predict the drought areas and prepare a mitigation plan. For this reason, the water balance process was applied to determine the water deficit areas at sub-district level in Thailand from 2019 to 2020. The water supplies were evaluated by measuring all the existing available water in rainfall-runoff, waterbodies, and watercourses. Furthermore, the water demands were calculated for domestic, agriculture, ecology, and industry sectors. The study results on water balance were in good agreement with drought areas as identified by the disaster management agency. Finally, we can conclude that the methodology used for this study is an efficient tool for the drought prediction at a sub-district level in the rainfed areas.